Personal Branding Mohammad Mahfud Md (Analisis Personal Branding Mahfud Md Dalam Pemilu 2024) - Calvin Antony; Shahibunnahar; Mellyana Candra (Lembaga Pengembangan Kinerja Dosen, 2024)
In politics, political branding is also increasingly important to create positive perceptions among general elections. In various election phases, information technology can be used to meet the needs of the KPU as an institution that manages the electoral process, as well as by election participants and the general public. General elections or PEMILU are a series of democratic processes to elect people's representatives or government officials directly by the citizens of a country. In ELECTIONS, eligible citizens have the right to cast their votes for candidates or political parties. Political parties are an important component in the political dynamics of a nation. A political figure who has branding that can strengthen his partner is Mahfud MD. This research uses quantitative analysis with a descriptive approach. The results of this research show what personal branding is and what Mahfud MD's personal branding looks like.